2024
DOI: 10.1186/s13073-024-01321-8
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-instructed microglia transition to heterogeneous phenotypic states with phagocytic and dendritic cell-like features in patient tumors and patient-derived orthotopic xenografts

Yahaya A. Yabo,
Pilar M. Moreno-Sanchez,
Yolanda Pires-Afonso
et al.

Abstract: Background A major contributing factor to glioblastoma (GBM) development and progression is its ability to evade the immune system by creating an immune-suppressive environment, where GBM-associated myeloid cells, including resident microglia and peripheral monocyte-derived macrophages, play critical pro-tumoral roles. However, it is unclear whether recruited myeloid cells are phenotypically and functionally identical in GBM patients and whether this heterogeneity is recapitulated in patient-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 88 publications
(195 reference statements)
0
1
0
Order By: Relevance
“…Single-cell profiling of patient-derived orthotopic xenograft models revealed that these models recapitulate the physiologically relevant glioblastoma ecosystem, with an intact blood–brain barrier and varying tumor niches within the TME [ 52 , 53 ]. However, these models are immunodeficient, missing the T cell component of the TME.…”
Section: Understanding Cns Tumors At a Single-cell Levelmentioning
confidence: 99%
“…Single-cell profiling of patient-derived orthotopic xenograft models revealed that these models recapitulate the physiologically relevant glioblastoma ecosystem, with an intact blood–brain barrier and varying tumor niches within the TME [ 52 , 53 ]. However, these models are immunodeficient, missing the T cell component of the TME.…”
Section: Understanding Cns Tumors At a Single-cell Levelmentioning
confidence: 99%